Transcriptomic insights into host transcriptional manipulation by ssDNA and ssRNA viruses in the marine planktonic diatom Chaetoceros tenuissimus - Yuki Hongo; Yuji Tomaru (Virus Research)
The marine diatom Chaetoceros tenuissimus coexists in the coastal ocean with two distinct viruses: a circular single-stranded DNA virus and a single-stranded RNA virus. Both viruses are capable of killing the host in vitro experiments; however, the molecular mechanisms by which host genes respond and are utilized by these viruses for replication and proliferation remain unclear. In this study, RNA-seq analyses were conducted to investigate these mechanisms, and the host transcripts specific to each virus were validated by RT-qPCR. In the early phase of infection, RNA-seq analysis revealed that gene transcription related to endocytosis, vacuolar acidification, and nitrogen metabolism was commonly upregulated. In contrast, genes related to transcription and translation were downregulated in cells inoculated with the DNA virus. In the later phase of infection, cells inoculated with the DNA and RNA viruses showed upregulation of genes related to DNA replication and packing, and autophagy, respectively. These virus-specific gene transcripts were confirmed to differ significantly by RT-qPCR. Chaetoceros tenuissimus has previously inserted a fragment of the DNA viral gene (EVLF) into its genome. Intriguingly, the transcription level of EVLF was upregulated in cells inoculated with the DNA virus as time progressed. Thus, regarding specific molecular responses, the DNA virus may hijack the host replication machinery to replicate its own genome, with EVLF playing a role in viral proliferation, whereas the RNA virus may hijack the autophagosome membrane to replicate its own genome, based on the observed replication of the related RNA virus at the membrane. This fundamental information provides insight into the diatom–virus infectious mechanism.